Existence of Solutions for Fractional Delay Integrodifferential Equations - Balachandran, K.; Kiruthika, S.; Rivero, M.; Trujillo, J.J. (Journal of Applied Nonlinear Dynamics, 2026)
n this article, we study the existence of solutions for a class of fractional integrodifferential equations with time varying delay by using the resolvent operators and fixed point technique. The main results present in this paper improve some results on this issue that have been studied recently. An example is provided to illustrate our main theoretical results.